Small-seeded Hakea species tolerate cotyledon loss better than large-seeded congeners. - El-Amhir, S.; Lamont, Byron; He, Tianhua; Yan, G. (Nature Publishing Group, 2017)
Six Hakea species varying greatly in seed size were selected for cotyledon damage experiments. The growth of seedlings with cotyledons partially or completely removed was monitored over 90 days. All seedlings perished by the fifth week when both cotyledons were removed irrespective of seed size. Partial removal of cotyledons caused a significant delay in the emergence of the first leaf, and reduction in root and shoot growth of the large-seeded species. The growth of seedlings of small-seeded species was less impacted by cotyledon damage. The rate of survival, root and shoot lengths and dry biomass of the seedlings were determined after 90 days. When seedlings were treated with balanced nutrient solutions following removal of the cotyledons, survival was 95-98%, but 0% when supplied with nutrient solutions lacking N or P or with water only. The addition of a balanced nutrient solution failed to restore complete growth of any species, but the rate of root elongation for the small-seeded species was maintained. Cotyledons provide nutrients to support early growth of Hakea seedlings, but other physiological roles for the cotyledons are also implicated. In conclusion, small-seeded Hakea species can tolerate cotyledons loss better than large-seeded species.